Análise do pré-mix de breu esterificado e policloreto de alumínio como agente de colagem interna em sistemas alcalinos - Santos, Ivan Rodrigues dos [UNESP] (2015)
The papers produced in alkaline systems shows better properties than those produced in acidic systems and enable the use of calcium carbonate as a filler. This research aimed to enable the use of a rosin based product as internal sizing agent in neutral/ alkaline system of papermaking process. Three studies were conducted research for the development of a new sizing agent, the differential being the esterification of rosin then pre-mixing with PAC (polyaluminium chloride) at different concentrations. The sizing agents were evaluated on papers made up of bleached ECF pulp industry, starch, cap and sizing agent. The sheets formed with the additives were evaluated for sizing efficiency (Cobb test, Edge Wickings peroxide, lactic acid and water) in paper coating line of paper card - 100 g/m². It was also conducted a study in industry through laboratory simulation. It's about the application from the sizing agent in the mass of paper machine covering layer #9 Klabin - Monte Alegre Unit. A second study aimed to evaluate the performance of different sequences pulp bleaching kraft-O2 eucalyptus in internal sizing of the surface layer of the paper card. Six different bleaching sequences, being four ECF's - D(E+P)DD; AHTD(E+P)DD; AHTD(E+P)DP; AHTDEDP, an ECF-Light - AHTD(PO)D and a new short bleaching sequence ECF - AHTDP are investigated. The pulps were bleached to 90 ± 0.5% ISO. The pulps were refined in PFI mill and refine the curve was determined by previous tests. The pulps held at 40 ° Schopper-Riegler (° SR). Thereafter, handsheets (100 g / m²) were formed with 10 kg/t industrial sizing agent plus 6 kg/t industrial PAC, at different pH ranges (7.0, 7.5, 8.0). Quality parameters analyzed were Cobb test, Edge Wickings peroxide, lactic acid and water. The results proved the efficiency of the new sizing agent to the parameters evaluated